Specifics of covering migration problems in regional printed mass media - A.Yu. Anisimov; D.V. Tumanov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The problem of creating an image of forced migrants in Russian regional printed mass media has been discussed. The articles on migration problems that were published in the newspapers “Nash Zelenyi Dol” and “Zelenodol'skaya Pravda” during the period of six months (from July to December 2014) have been analyzed. The following parameters have been studied: newsbreak, frequent lexical units, connotative elements, and genre characterization of materials. As a result of the analysis, it has been concluded that mass media of small Russian towns are highly tolerant to migrants. In particular, they are often described by such neutral lexical units as “refugees”, “displaced persons”, “citizens (of a country)”, and “migrants”, all having a positive connotation. We believe that mass media play an important role under the conditions of international instability in Russia, including the Republic of Tatarstan. On the one hand, they can act as catalysts of the emerging conflict. On the other one, they can instil respect for refugees in the recipient society and contribute to their further social adaptation.